Neuroglobin Expression Models as a Tool to Study Its Function - Luyckx, Evi (Oxid Med Cell Longev, 2019)
Neuroglobin (Ngb) is an evolutionary conserved member of the globin family with a primary expression in neurons of which the exact functions remain elusive. A plethora of in vivo and in vitro model systems has been generated to this day to determine the functional biological roles of Ngb. Here, we provide a comprehensive overview and discussion of the different Ngb models, covering animal and cellular models of both overexpression and knockout strategies. Intriguingly, an in-depth literature search of available Ngb expression models revealed crucial discrepancies in the outcomes observed in different models. Not only does the level of Ngb expression—either physiologically, overexpressed, or downregulated—alter its functional properties, the experimental setup, being in vitro or in vivo, does impact the functional outcome as well and, hence, whether or not a physiological and/or therapeutic role is ascribed to Ngb. These differences could highlight either technical or biological adaptations and should be considered until elucidation of the Ngb biology.